Development of General Biology Learning E-Modules Based on Constructivism - Rukmana, Musma; Andre Watung, Fernando; Hasmiati, Hasmiati; Putri Agustina, Tika; Restutiningsih Putri Utami, Aisyiah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
Higher education must adapt its educational practices to ICT, which is now developed rapidly. There are many different approaches, and constructivism-based e-module development is an alternative. This research used the R&D method by adapting the ADDIE development model, which aimed to produce constructivism-based e-module products that meet the criteria of being valid, effective, and practical for use in the learning process. The e-module developed was validated using an expert validation questionnaire filled out by two expert validators, with a result of 4.32, which was included in the valid category. The effectiveness of the e-module was obtained by 100% of students achieving learning completeness scores and increasing learning outcomes based on a normalized gain analysis of 0.71 (high category). The results of the e-module practicality test showed positive student responses, where 86.67% of statements were included in the very strong category and 13.33% in the strong category. Based on the research results, it can be concluded that the constructivism-based general biology learning e-module developed is valid, practical, and effective.